El uso del mapa de incidentes críticos y la narración para reflexionar sobre el aprendizaje musical - Pamela Burnard (Ediciones Complutense, 2005)
What students say about musical learning speaks to the problems they have in trying to commit themselves to learning. This article addresses aspects of what musically matters to children at primary school and when they move from pri-mary to 'the big' school, and to teacher trainees and experienced teachers in becoming teachers of music. The use of critical incident charting is reported as drawn from datasets comprising interviews with young people aged between 12 and 16 and with pre- and in-service teachers. The article concludes with some ways in which music educators can en-gage in more reflective practice in school.